Concomitant Marked Decline in Prevalence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and Other Respiratory Viruses Among Symptomatic Patients Following Public Health Interventions in Australia: Data from St Vincent's Hospital and Associated Screening Clinics, Sydney, NSW. (25th August 2020) - Marriott, Deborah; Beresford, Rohan; Mirdad, Feras; Stark, Damien; Glanville, Allan; Chapman, Scott; Harkness, Jock; Dore, Gregory J; Andresen, David; Matthews, Gail V
Abstract: Our Australian hospital tested almost 22 000 symptomatic people over 11 weeks for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a multiplex polymerase chain reaction (PCR) assay. Following travel bans and physical distancing, SARS-CoV-2 and other respiratory viruses diagnoses fell dramatically. Increasing rhinovirus diagnoses as social control measures were relaxed may indirectly indicate an elevated risk of coronavirus disease 2019 (COVID-19) resurgence.